Destinos interrompidos: uma análise netnográfica do luto por morte em sinistro de trânsito - Duccini, Bianca Elisa Fogaça (2023)
Traffic crashes were responsible for 32,652 deaths in 2021 in Brazil, having been the leading cause of death of young people between 15 and 29 years old. The present research is anchored on theoretical approximations among fundamentals about grief and Heideggerian thought. Grief over violent death presents specificities in the human experience of loss, emphasizing that the type of death represents a risk factor for complications in the grieving process. The objective of this research was to analyze writings addressed to people who died of violent death in traffic crashes, shared on the social network Facebook. The netnographic method was used with a hermeneutic interpretation of the data obtained about what was communicated in the post made, why it was posted in that specific community, and what was communicated beyond the written. The results indicate that special dates, kinship level, longing, love permanence, remembrance, alcohol consumption, driver irresponsibility, and hopelessness are the main contents of the posts. As for the motivation for writing in the specific community, the results pointed to the feeling of belonging and reception. The statement apart from the writing was about remembering not only to miss the deceased but to evoke the responsibility of the drivers who victimized his family and friends and the quest for justice. The cyberspace traveled in the research offered possibilities for its realization, with a focus on the experience of grieving, reinforcing the importance of methodological adequacy to contemporary resources